Tapered discontinuation vs. maintenance therapy of antipsychotic medication in patients with first-episode schizophrenia: Obstacles, findings, and lessons learned in the terminated randomized clinical trial TAILOR - Stürup, Anne Emilie; Hjorthøj, Carsten; Albert, Nikolai; Dolmer, Signe; Birk, Merete; Ebdrup, Bjørn H.; Eplov, Lene Falgaard; Jensen, Heidi; Vernal, Ditte Lammers; Speyer, Helene; Mors, Ole; Nordentoft, Merete (Frontiers in Psychiatry, 2022)
Aim Evidence is insufficient regarding the consequences of discontinuing vs. maintaining antipsychotic medication in patients with first-episode schizophrenia. Our aim was to examine tapered discontinuation vs. maintenance treatment regarding remission of psychotic symptoms and impact on other areas. Methods Patients included had a diagnosis of schizophrenia, were treated with antipsychotic medication, and were in remission of psychotic symptoms. Participants were randomized to tapered discontinuation or maintenance treatment with antipsychotic medication. Assessments were undertaken at baseline and after 1-year. The primary outcome was remission of psychotic symptoms without antipsychotic medication. Results The trial was terminated due to insufficient recruitment. In total, 29 participants were included: 14 in the tapering/discontinuation group and 15 in the maintenance group. Adherence to maintenance treatment was poor. At 1-year follow-up, remission of psychotic symptoms without antipsychotic medication for 3 months was observed in five participants in the tapering/discontinuation group and two in the maintenance group. Conclusion Due to insufficient recruitment this study does not provide a conclusion on whether unfavorable outcomes or advantages follow tapering of antipsychotic medication. Recruitment and adherence to maintenance treatment encountered obstacles. Based on experiences from this trial, we discussed alternative study designs as consistent evidence is still needed on whether to continue or discontinue antipsychotic medication in remitted patients with first-episode schizophrenia. Clinical trial registration https://www.clinicaltrialsregister.eu/ctr-search/trial/2016-000565-23/DK, EU Clinical Trials Register—EudraCT no. 2016–000565–23.